1963
DOI: 10.1017/s0022172400020933
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic differences between strains of foot-and-mouth disease virus of type SAT 1

Abstract: Antigenic differences between the strains RV 11 and SA 13/61 of foot-and-mouth disease virus (type SAT 1) were studiedin vivoby cross-protection tests. Cattle inoculated with formolized antigen of either strain developed good immunity to experimental infection with the identical strain but little resistance to the other strain.In vitrothe results of complement fixation tests and of serum-virus neutralization tests in tissue culture were consistent with the observations madein vivo. The results of studies on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

1964
1964
1991
1991

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…For example, strains SA 13/61 and SWA 40/61, both isolated in the same year, though showing some antigenic resemblance were nevertheless demonstrably different from one another and differed to a much greater extent from the 'older' strain, RVII (Hyslop et al 1963), and also from the Middle East strain Isr. 4/62 (Hyslop, unpublished result).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…For example, strains SA 13/61 and SWA 40/61, both isolated in the same year, though showing some antigenic resemblance were nevertheless demonstrably different from one another and differed to a much greater extent from the 'older' strain, RVII (Hyslop et al 1963), and also from the Middle East strain Isr. 4/62 (Hyslop, unpublished result).…”
mentioning
confidence: 96%
“…Reports of effects of this diversity were reviewed briefly in a recent paper (Hyslop, Davie & Carter, 1963 passaged serially by inoculating clarified suspensions of epithelium into the mucosa of the tongues of partially immunized cattle. In the early passages a 1/10 suspension was employed, but later the dilution was increased to 1/1000, then to 1/10,000 and finally to 1/100,000.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent work at this Institute was directed to the correlation of the results obtained by cross-vaccination, cross-serum neutralization and cross-complement fixation tests. In the first of these experiments Galloway, Davies & Smith, 1962;Hyslop, Davie & Carter, 1963; and unpublished work) has confirmed that there are strains of virus of the same immunological type which can be classified as antigenic variants or subtypes within the types and that in general there is good correlation between the results of the three tests. The results of the two serological tests and the cross-vaccination tests showed that three of the ten pairs were of the same subtype and that seven of them were dissimilar.…”
mentioning
confidence: 80%
“…Evidence of the existence of different subtypes within the seven principal types of foot-and-mouth disease (FMD) virus was described by Hyslop, Davie & Carter (1963). Recently we reported the isolation of an immunologically distinct variant strain of virus of type SAT 1, which evolved when strain Tur.…”
mentioning
confidence: 99%